Rest and exercise oxygen uptake and cardiac output changes 6 months after successful transcatheter mitral valve repair - Carlo Vignati; Fabiana De Martino; Manuela Muratori; Elisabetta Salvioni; Gloria Tamborini; Antonio Bartorelli; Mauro Pepi; Francesco Alamanni; Stefania Farina; Gaia Cattadori; Valentina Mantegazza; Piergiuseppe Agostoni (ESC Heart Failure, 2021)
Abstract Aims Changes in peak exercise oxygen uptake (VO2) and cardiac output (CO) 6 months after successful percutaneous edge‐to‐edge mitral valve repair (pMVR) in severe primary (PMR) and functional mitral regurgitation (FMR) patients are unknown. The aim of the study was to assess the efficacy of pMVR at rest by echocardiography, VO2 and CO (inert gas rebreathing) measurement and during cardiopulmonary exercise test with CO measurement. Methods and results We evaluated 145 and 115 patients at rest and 98 and 66 during exercise before and after pMVR, respectively. After successful pMVR, significant reductions in MR and NYHA class were observed in FMR and PMR patients. Cardiac ultrasound showed reverse remodelling (left ventricular end‐diastolic volume from 158 ± 63 mL to 147 ± 64, P < 0.001; ejection fraction from 51 ± 15 to 48 ± 14, P < 0.001; pulmonary artery systolic pressure (PASP) from 43 ± 13 to 38 ± 8 mmHg, P < 0.001) in the entire population. These changes were significant in PMR (n = 62) and a trend in FMR (n = 53), except for PASP, which decreased in both groups. At rest, CO and stroke volume (SV) increased in FMR with a concomitant reduction in arteriovenous O2 content difference [ΔC(a‐v)O2]. Peak exercise, CO and SV increased significantly in both groups (CO from 5.5 ± 1.4 L/min to 6.3 ± 1.5 and from 6.2 ± 2.4 to 6.7 ± 2.0, SV from 57 ± 19 mL to 66 ± 20 and from 62 ± 20 to 69 ± 20, in FMR and PMR, respectively), whereas peak VO2 was unchanged and ΔC(a‐v)O2 decreased. Conclusions These data confirm pMVR‐induced clinical improvement and reverse ventricular remodelling at a 6‐month analysis and show, in spite of an increase in CO, an unchanged exercise performance, which is achieved through a ‘more physiological’ blood flow distribution and O2 extraction behaviour. Direct rest and exercise CO should be measured to assess pMVR efficacy.